2018
DOI: 10.1093/sysbio/syy014
|View full text |Cite
|
Sign up to set email alerts
|

When Darwin’s Special Difficulty Promotes Diversification in Insects

Abstract: Eusociality, Darwin's special difficulty, has been widely investigated but remains a topic of great debate in organismal biology. Eusocial species challenge existing theories, and the impact of highly integrated societies on diversification dynamics is controversial with opposing assertions and hypotheses in the literature. Here, using phylogenetic approaches in termites-the first group that has evolved eusociality-we assessed the fundamental prediction that eusocial lineages have higher diversification rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…Rather they reflect complex interacting historical processes, which is perhaps not surprising given the long-term accumulation of the diversity in the region. This result is also consistent with other studies such as that explaining the biogeography of the amphibians and reptiles in Madagascar as well as those explaining the rapid diversification in Andean bellflowers (Lagomarsino et al, 2016) and insects (Legendre & Condamine, 2018).…”
Section: No Dominant Single Hypothesis For Patterns Of Diversitysupporting
confidence: 93%
“…Rather they reflect complex interacting historical processes, which is perhaps not surprising given the long-term accumulation of the diversity in the region. This result is also consistent with other studies such as that explaining the biogeography of the amphibians and reptiles in Madagascar as well as those explaining the rapid diversification in Andean bellflowers (Lagomarsino et al, 2016) and insects (Legendre & Condamine, 2018).…”
Section: No Dominant Single Hypothesis For Patterns Of Diversitysupporting
confidence: 93%
“…The diversity of Holometabola has been explained in the context of adaptive radiation on flowering plants ( Farrell 1998 ), radiation through parasitism ( Forbes et al 2018 ), and eusocial behavior ( Legendre and Condamine 2018 ) as well as the key innovation of the group—complete metamorphosis. Among the holometabolan lineages, it is possible key innovations have driven partnership with gut bacteria ( Moran et al 2019 ).…”
Section: Host Lineagementioning
confidence: 99%
“…They are dominant animals in the soil, comprising up to 40-65% of the total soil macrofaunal biomass (Eggleton et al, 1996;Tuma et al, 2020), and can be responsible for 54-68% of total decomposition in some biotopes (Jouquet et al, 2011;Ashton et al, 2019). Despite the important ecological role of termites on a variety of terrestrial ecosystems, our understanding of the adaptations that led to such high prevalence is still limited (Davis et al, 2009;Legendre and Condamine, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Legendre and Condamine (2018) used parametric methods to explore large-scale diversification patterns in Dictyoptera and found evidence for two main rate shifts: one at the origin of termites (with eusociality) and another at the origin of Termitidae (with the loss of cellulolytic parabasalids symbionts). They also found that lineages with true workers diversified faster than those with pseudergates ("false" workers).…”
Section: Introductionmentioning
confidence: 99%